Analisis Perbandingan Pemetaan Ekosistem Bentik Menggunakan Allen Coral Atlas dan Sentinel-2 di Kepulauan Pagai - Syarifudin Nur; Susanna Nurdjaman; Muhammad Abia Saefulloh (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2025)
Benthic ecosystem is a crucial component of coastal ecosystems, making its protection essential for maintaining ecosystem health. This study presents a comparative analysis of benthic mapping in the Pagai Islands, West Sumatra Province. It utilizes two different satellite imagery sources: the Allen Coral Atlas, derived from Planet Labs' Dove satellites with a spatial resolution of 3-5 meters, and Sentinel-2 imagery from ESA's Copernicus program, with a resolution of 10 meters, both acquired from 2024. The Allen Coral Atlas data were processed using Google Earth Engine and visualized in QGIS, while Sentinel-2 data were processed in Snap and QGIS, covering the same period. In situ validation used secondary field data from six stations across North and South Pagai Islands. This data was used to validate seagrass, mangrove and coral reef presence and identify species in their natural habitats. The analysis revealed strong similarity between both maps, particularly for seagrass habitats, though minor discrepancies occurred in cloud-covered and sediment-affected areas. This highlights the reliability of both datasets for benthic mapping, with greater potential than simple validation. They can be applied to track annual fluctuations in seagrass distribution, monitor mangrove extent and recovery, and evaluate coral reef area and degradation. Such analyses provide robust support for ecological research and management in the dynamic Pagai Islands.